Análisis hermenéutico de la ley 31751 y su confrontación con la jurisprudencia de la Corte Suprema peruana en el ámbito penal 2023 – 2024 - Cardama Casique, Maria Magdalena (2025)
This research paper provides an in-depth interpretation of Law 31751, enacted on May 26, 2023, which regulates the suspension of the criminal statute of limitations in the Peruvian legal system (2023-2024). The justification lies in the need to harmonize it with constitutional principles and the jurisprudence of the Supreme Court, thereby affirming legal certainty and due process, especially in corruption offenses. The objective was to examine, using a qualitative hermeneutic approach and a grounded theory design based on Strauss & Corbin (1990), the conflict between the law and its application, proposing harmonization guidelines.Through documentary analysis and hermeneutic methods (literal, systematic, historical, teleological) according to Gadamer (1977), various core categories emerged, such as "Access to Justice and Fundamental Rights," "Normative and Procedural Analysis," and "Implications and Proposals." Codes such as "Legal Uncertainty," "Procedural Guarantees," and "Temporal Limitations" revealed tensions with proportionality and the right to a trial without delay, disrupting legal coherence and institutional trust (Martínez Huamán, 2023; Contreras Campos, 2023).The Theory of Dynamic Equilibrium in Normative Application is proposed, suggesting a dynamic balance between criminal prosecution and fundamental rights, mediated by interpretive flexibility. It is concluded that it is urgent to establish uniform interpretive criteria, make the suspension period more flexible, and monitor its impact, balancing the rights of defendants and victims (Noronha Val, 2024; Dworkin, 1986).